Fractures and disruptions in children's literature: From print to screen and back with Isabel Minhós Martins - Melão, Dulce (2015)
Recent years have seen a (r)evolution in children’s literature in Portugal, with particular emphasis on the picturebook, perhaps echoing the challenges of a society where page and screen are providing us new ways of seeing and listening to the world. In order to meet these challenges, educators increasingly need to promote a myriad of ways to motivate children to become lifelong readers. Isabel Minhós Martins recent picturebooks (2013) Este livro está a chamar-te (não ouves?) (This book is calling you (don’t you hear?) and Uma onda pequenina (A tiny wave) invite readers to follow such thought-provoking paths, calling them to interact with printed words mingled with a proposed “digital reading experience”, embracing fractures and disruptions that come along. The objectives of this paper are twofold: i) to briefly review the growing importance of the picturebook in education, namely in school selections (Plano Nacional de Leitura - National Reading Plan); ii) to explore how the interaction between text and image might create fractures and disruptions, allowing creativity to thrive and thus contributing to increase children’s motivation to read. It is hoped that such ways of reading pave the way for many more to come.